Evolution of 'pay-it-forward' in the presence of the temptation to free-ride - Satoshi Uchida; Tatsuya Sasaki; Hitoshi Yamamoto; Isamu Okada (Games, 2024)
Paying it forward' is a behavior in which people help someone else because they were helped in the past. Although experimental evidence exists that indicates that real human beings often 'pay-it-forward' even in the face of free-rider risks, the theoretical basis for the evolution of this behavior remains unclear. In this paper, we propose a game-theoretical model that explains how pay-it-forward behavior can evolve despite the temptation to free-ride. By assuming that human beings exhibit cognitive distortions, as predicted by prospect theory, and that free-riding is punished with a tiny probability, we demonstrate that pay-it-forward, alongside unconditional altruistic behavior, can evolve and effectively deter free-riding behavior.
Keywords: 330; cooperation; evolutionary game theory; expected utility theory; pay-it-forward; prospect theory; punishment; social dilemma